2010
DOI: 10.1080/09593330903514466
|View full text |Cite
|
Sign up to set email alerts
|

The fate of Cu, Zn, Pb and Cd during the pyrolysis of sewage sludge at different temperatures

Abstract: In the present study, a sequential extraction procedure, recommended by the Community Bureau of Reference (BCR), was used for the fractionation of the heavy metals Cu, Zn, Pb and Cd in sewage sludge and its residues produced after pyrolysis at different temperatures from 250 to 700 degrees C. The results show that, in the sludge sample, the sum of the percentages of the reducible and oxidizable fractions for all metals except Cu was very high (65.4% for Cd, 85.7% for Pb, 78.7% for Zn), whereas the sum of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 28 publications
4
40
0
4
Order By: Relevance
“…However, its application to soil may sometimes be risky because of the potential presence of pathogenic organisms and heavy metals (HE et al, 2010). Thermal treatment of sewage sludge through pyrolysis produces biochar, reducing volume and organic contaminant characteristics (LIU et al, 2014) Silva et al…”
Section: Introductionmentioning
confidence: 99%
“…However, its application to soil may sometimes be risky because of the potential presence of pathogenic organisms and heavy metals (HE et al, 2010). Thermal treatment of sewage sludge through pyrolysis produces biochar, reducing volume and organic contaminant characteristics (LIU et al, 2014) Silva et al…”
Section: Introductionmentioning
confidence: 99%
“…Based on the obtained own results, the thermal treatment process favored the increase in contents of forms of some of the studied trace elements extracted with water. It resulted from a loss of unstable aliphatic bonds and formation of more stable aromatic bonds [39,40]. According to Hossain et al [11], despite an increase in the total content of trace elements as a result of pyrolysis of sewage sludge, the content of bioavailable forms did not change significantly.…”
Section: Chemical Composition Of the Materialsmentioning
confidence: 99%
“…Based on our study results, we found that the process of thermal conversion of organic materials did not cause mobilisation of available forms of most of the studied trace elements. Research results published by He et al [40] indicate that thermal conversion of organic materials results in a greater stability of such trace elements as Cd, Pb, Zn, and Cu.…”
Section: Elemental Composition Of Biocharsmentioning
confidence: 99%
“…In the studies conducted by Yachigo and Sato [39], higher pyrolysis temperature resulted in a considerable increase in the zinc and copper contents in the resulting material, but it did not change the cadmium content. In the view of He et al [40], the pyrolysis temperature exceeding 350°C results in a greater stability of such trace element as Cd, Pb, Zn and Cu. This phenomenon occurs due to the loss of unstable aliphatic connections and creation of more stable aromatic connections [41].…”
Section: Elemental Composition Of Biocharsmentioning
confidence: 99%